Numerical prediction of limiting draw ratio and thickness variation in hydromechanical deep drawing. (1st September 2004) - Singh, Swadesh Kumar; Kumar, D. Ravi
Hydromechanical deep drawing is a process for producing cup shaped parts with the assistance of a pressurised fluid. In the present work, a complete experimental set up has been designed and fabricated to conduct hydromechanical deep drawing on a 315 tonne hydraulic press. Limiting draw ratio has been determined by using blanks of various diameters. The process was simulated using explicit finite element code LSDYNA. A comparison was made between simulated and experimental results of conventional and hydromechanical deep drawing using low carbon steel sheets of extra-deep drawing grade of 0.96mm thickness. The simulated results showed reasonable agreement with the experimental data. It was found that by hydromechanical deep drawing higher drawability and more uniform thickness distribution could be obtained when compared to conventional deep drawing.